Manipulated structural variability affects the habitat choice of two ground-living beetle species in a laboratory experiment - Nittérus, Karolina; Gunnarsson, Åsa; Gunnarsson, Bengt (Entomologica Fennica, 2008)
The habitat choice of two ground-living carabid beetle species (Pterostichus oblongopunctatus (Fabricius) and Carabus hortensis Linneaus) was investigated in a laboratory experiment. Beetles were released in test arenas with two options of manipulated structural variability on the ground, i.e.; bare ground spots versus spots with logging residue (slash). Beetles were studied for 600 seconds and the total time spent on bare ground versus in slash was measured. The results revealed a preference for slash covered ground amongst the investigated beetles. Regardless of species or type of release spot (in the middle of the bare ground or in slash), the carabids resided significantly longer in slash compared with the bare ground. The results support recent studies emphasizing the importance of microhabitat variability for the abundance distribution of arthropods inmanaged systems.